Gradual Reforms of Capital Income Taxation - Howitt, Peter; Sinn, Hans-Werner (American Economic Review, 1989)
This paper analyzes the intertemporal allocation effects of anticipated tax-rate changes, reconsidering the recommendations of the Meade Committee in a perfect foresight general equilibrium model of economic growth. We show that the R-base (or consumption) tax can be more distortionary than an income tax and that a revenue-neutral integration of corporate and personal taxation may lower social welfare. Moreover, we argue that a dividend tax dominates the R-base tax because it places its distortions on the financial rather than on the real side of the economy.